Delamination resistant composites by interleaving bio-based long-chain polyamide nanofibers through optimal control of fiber diameter and fiber morphology. (16th June 2020) - Meireman, Timo; Daelemans, Lode; Rijckaert, Sander; Rahier, Hubert; Van Paepegem, Wim; De Clerck, Karen
Abstract: In this work an innovative electrospinning system is proposed that simultaneously has an adequate temperature resistance, a high increase in mode I (+51%) and mode II (+96%) delamination performance and can be commercially produced. Interleaving nanofibrous veils can potentially solve the issue of the limited delamination resistance encountered in composite laminates, but industrial upscaling has always been impeded by one or more critical factors. These constraining factors include a limited temperature stability of the nanofibers, a lack in simultaneous mode I and II delamination performance increase and the complexity of the electrospinning system because non-commercial polymers or specialty nanofibers (e.g. coaxial) are required. In this paper, a robust electrospinning system is proposed that is the first to overcome all major hurdles to make nanofiber toughening industrially viable. A new class of nanofibers based on biosourced polyamide 11 and its poly(ether-block-amide) co-polymers is used to deal with those shortcomings. The nanofibers have tuneable diameters down to 50 nm and cross-section morphologies ranging from circular to ribbon-shaped. The key to this work is the fundamental underpinning of the toughening effect using a broad range of interleaves with different mechanical and thermal properties, fiber diameters and fiber morphologies, all produced from the same bio-based base polymer. Generally, round and thin nanofibers performed better than larger and ribbon-like fibers. The relationship between the fiber morphology and the delamination performance is further underpinned using detailed analysis of the fracture surface. Ultimately, this results in a range of optimized nanofibrous veils capable of improving the delamination resistance considerably without suffering from the aforementioned drawbacks. Graphical abstract: Image 1